Stereotypical Image of Chinese People in Hollywood’s The Karate Kid 2010 Movie - Jihan Aurdania Sunardi; Ali Mustofa (Wanastra: Jurnal Bahasa dan Sastra, 2021)
Hollywood is an important media for the United States in spreading Western ideology. The hundreds years, Hollywood has featured various characters from different cultures and countries. However, they have suffered from cultural racism along with other minority groups. In American movie, the East depicted as ignorant and backward with a considered inferior culture compared to the west. This situation is known as orientalism, has influenced and controlled the mass media (films) and Western society's perceptions. This study aims to determine how eastern culture is depicted in the American film, The Karate Kid. This study uses Edward Said's Orientalism theory, which explained how the westerner views the east. The analysis concludes that the Hollywood industry reflects the superiority of the west over China through the character of Dre Parker. Hence, the portrayal of Chinese characters is displayed with stereotypes such as yellow faces, skin color racism, slanted eyes, bullying, and alcoholic habit.